Investigate the nutritional status, including body composition, of oncology patients attending an outpatient clinic at Groote Schuur hospital: a cross-sectional study - Blacker, Megan (Department of Human Biology, 2024)
Background There is an increase in cancer prevalence globally with an increase in cancer mortality in South Africa. Malnutrition, cancer cachexia and sarcopenia are conditions commonly experienced by people with cancer. Not only is there a deterioration of nutritional status, but these conditions are also known to have negative clinical and patient outcomes that include a decreased quality of life and functional status, increased hospital length of stay, increased treatment toxicity, reduced efficacy of anticancer treatments and an association with depression. Even though there is a greater understanding of the aetiology of cancer cachexia over recent decades, there has not been a global adoption of a definition and a framework for identification of cancer cachexia. Therefore, there is no standardisation of research to compare results related to prevalence and multimodal interventions which hampers implementation of awareness and identification of and treatment for cancer cachexia. The Global Leadership Initiative on Malnutrition (GLIM) identifies and classifies malnutrition across different health care settings. Recently suggested cancer guidelines identified cancer cachexia using amended GLIM diagnostic criteria. With sarcopenia identification, there have been American, Asian and European formulated guidelines with variation in the diagnostic criteria used. This makes it challenging for other countries not represented to create awareness and identification of sarcopenia in different healthcare settings. Gold standard methods in body composition, namely computer tomography (CT) and magnetic resonance imaging (MRI), and reference standard methods, namely dual energy X-ray absorptiometry (DEXA) have highlighted the common phenotypic component of reduced muscle mass in malnutrition, cancer cachexia and sarcopenia, with a plethora of reference populations used and cutoff points determined for different representations of muscle mass. This variety in research has added to the challenges of identifying reduced muscle mass, particularly in resource limited healthcare settings that do not have access to expensive CT, MRI and DEXA scans and relevant reference populations. Therefore, there is a need to identify alternative methods to identify reduced muscle mass earlier in the cancer journey that need to be cheap, accessible, easy to use within the South African health setting. These alternative methods will be helpful in the identification of malnutrition, sarcopenia and cancer cachexia. Aims The first aim was to investigate body composition, with particular focus on muscle mass, using DEXA as the reference standard in this sample of cancer patients, in relation to nutritional status indicators and alternative muscle mass markers. The second aim was to investigate malnutrition in cancer outpatients according to Global Leadership Initiative on Malnutrition (GLIM) using different approaches, including technical (DEXA) and clinical approaches to determine muscle mass. The third aim was to investigate sarcopenia in cancer outpatients according to the newest diagnostic guidelines from the European Working Group on Sarcopenia in Older People (EWGSOP) using muscle mass determined from DEXA (reference standard) and alternative muscle mass markers. The fourth aim was to investigate cancer cachexia using different diagnostic frameworks and the associations with nutritional status indicators in cancer outpatients. Method The study followed a quantitative, cross-sectional design where data were collected over 2 days and twenty-eight eligible cancer patients were recruited through consecutive sampling from colorectal, head and neck, ear, nose and throat oncology outpatient clinics at Groote Schuur Hospital (GSH). A two-phase questionnaire was developed for the purposes of this study where sociodemographic, clinical and cancer related data, biochemistry, physical activity, dietetics related data, a twenty-fourhour recall and semi-quantitative food frequency questionnaire information were collected. On the second data collection day, handgrip strength (HGS), nutrition risk screening-2002 (NRS-2002), patient generated subjective global assessment (PG-SGA), a second a twenty-four-hour recall, alternative muscle mass markers [mid upper arm circumference (MUAC), calf circumference (CC), corrected arm muscle area (cAMA), estimated appendicular skeletal muscle (est ASM), global physical examination (GPE)] and DEXA measurements were collected. Results There is a high prevalence of reduced muscle mass (82.1%) as determined by our reference standard, DEXA, expressed as ASM. From the six alternative muscle mass markers, calf circumference performed best across the different statistical tests in comparison to the reference standard, DEXA. Calf circumference demonstrated fair agreement related to Cohen's kappa, overall fair for sensitivity (73.9%) / specificity (80%) and a percentage agreement of 78.6%. Our results suggest that calf circumference may be used to screen cancer patients to determine those without RMM as the specificity was 80% i.e., only 20% of participants without RMM will be incorrectly categorised. None of our nutritional status indicators can be used as proxies for detecting reduced muscle mass. BMI, scored NRS-2002 and scored PG-SGA were statistically significant in participants identified with reduced muscle mass. Our study confirmed that malnutrition is prevalent in this cancer population ranging from 75.0% to 92.9% depending on the muscle mass assessment method and Global Leadership Initiative on Malnutrition (GLIM) approach used. Out of the six alternative muscle mass markers and not having muscle mass phenotype, calf circumference demonstrated good agreement related to Cohen's kappa, overall fair for sensitivity (73.9%) / specificity (80%) and a percentage agreement of 92.9% suggesting that it may be used as an alternative muscle mass phenotype in the GLIM diagnostic criterium for reduced muscle mass. We found a prevalence of sarcopenia from 7.4% to 18.5%, depending on the muscle mass method used Of the five alternative muscle mass markers, calf circumference agreed perfectly and had 100% sensitivity and specificity. We found that the diagnosis and classification of cancer cachexia varied depending on the diagnostic models used. We used two diagnostic models to identify pre-cachexia and found a range of 17.9% to 28.6%. We used four diagnostic models to identify cancer cachexia and found a range from 45.8% to 82.1%. None of the three diagnostic cancer cachexia frameworks performed well when compared to the most recent cancer cachexia framework adapted from GLIM. In addition, none of our nutritional status indicators performed well across all the different tests when compared to the recent cancer cachexia framework. Therefore, suggesting that our routine use of nutritional status indicators within practice, may not be sufficiently sensitive, specific and agree with our reference framework to diagnose cancer cachexia. Only handgrip strength and albumin are significantly different in the cancer cachexia group. In conclusion, despite our limitation regarding small sample size, calf circumference may be a possible alternative muscle mass marker to screen for reduced muscle mass, may be used as a proxy in the GLIM diagnostic criteria and for sarcopenia diagnosis. As cancer cachexia is recognized as a multifactorial and multi-organ syndrome, all diagnostic components may need to be present, therefore simplistic commonly used clinical and practical approaches may not be adequate to detect cancer cachexia early in the cancer patient's journey.